TELAAH PENTINGNYA PROFILING PESERTA DIDIK BAGI GURU SEKOLAH DASAR DALAM MENDUKUNG PEMBELAJARAN INKLUSIF - amalia putri, tarisa; Yuniarti Rahayu; Siska Suci Lestari; Susilawati; Ilah Nurlaelah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the importance of student profiling for elementary school teachers in supporting inclusive learning. The method used was a literature review employing a qualitative descriptive approach to national and international journal articles published between 2019 and 2025. The data was obtained from Google Scholar and various scientific journal databases using relevant keywords. The data analysis technique used is content analysis. The study findings indicate that student profiling plays a crucial role in helping teachers understand the diversity of students’ characteristics, learning styles, interests, and learning needs. Profiling, which involves mapping characteristics and conducting diagnostic assessments, has been shown to help teachers design more adaptive and student-centered instruction. In addition, student profiling is closely linked to the implementation of differentiated instruction and inclusive education, which can accommodate all students equally. Profiling also has a positive impact on increasing student engagement and motivation to learn. Therefore, student profiling is a strategic step that elementary school teachers must take before teaching in order to create a learning environment that is inclusive, flexible, and responsive to the needs of each student.